How doy ou solve #2v - 4+ 2( 4v + 6) = - 2( v + 5)#?

1 Answer
Sep 24, 2016

Answer:

# v = -3 / 2 #

Explanation:

# 2v - 4 + 2(4v + 6) = -2(v + 5) #

First step: expand brackets - you do this by multiplying the number in front of the brackets by each of the numbers in the brackets.

# 2v - 4 + 2(4v) + 2(6) = -2(v) - 2(5) #
# 2v - 4 + 8v + 12 = -2v - 10 #

Second step: move all letters on one side and all numbers on the other side.
Note: when moving numbers/letters on the opposite side of the equal sign, you have to change signs ie. # 2v = -1v + 3 # would turn into 2v + 1v = 3
Also note: it doesn't matter what side you move the letters and numbers, as long as they are both on different sides.

# 2v + 8v + 2v = -10 + 4 - 12 #

Third step: simplify both sides.

# 12v = -18 #

Fourth step: isolate v by dividing 12 onto the opposite side. We divide because the opposite of multiply is divide and 12 is multiplied by v.

# v = -18 / 12 #

Fifth step: simplify further or leave as above.

# v = -3 / 2 #

To get -3 and 2, I divided -18 and 12 by the highest common factor which was 6.